Pengaruh Model Project Based Learning Terhadap Hasil Belajar Siswa Pada Materi Kubus Dan Balok - Herianto, Herianto; Pomalato, Sarson W.Dj.; Abdullah, Abdul Wahab (Scimadly Publishing, 2024)
This article discusses the effect of the project-based learning model on student mathematics learning outcomes in cube and block material with the aim of knowing the differences in student learning outcomes taught using project-based learning models and learning outcomes using direct learning models on cube and block material. The method used is the experimental method with the Posttest only control group design design. The sampling technique uses simple random sampling, and the data collection technique is by administering a learning achievement test in the form of an essay. The results showed that there were differences in the learning outcomes of students who were taught using the project-based learning model and the learning outcomes of students who were taught using the direct learning model where the learning outcomes of students who were taught using the project-based learning model were higher than the learning outcomes of students who were taught using direct learning models on cube and block material. Project-based learning can increase student activity and student motivation in learning that aims to provide an understanding of critical, creative and innovative thinking.